Importancia de los bioestimulantes en el cultivo de papaya (Carica papaya - Lamilla Burbano, Erick Adrián (2020)
The papaya is a product that is currently becoming very important, this would benefit farmers to improve their economic status. In the equator, papaya has different presentations for its consumption, either in jams or in juices or in its own fruit. For a papaya harvest there must be an optimal management of nutrients, where the bio-stimulants are of great importance and help at the moment of their assimilation; therefore this will allow to obtain resistant, strong and more vigorous plants where the production yield will increase, their resistance to diseases will help to diminish the deficits of dead plants. For the development of this document, bibliographic information was collected from digital and physical books, magazines, scientific articles, web pages, papers, technical manuals. The information obtained was made through the technique of analysis, synthesis and summary, with the purpose that the reader knows about the importance of the application of organic biostimulants for the stimulation of the development of the fruit of the papaya cultivation. For the previously detailed, it was determined that For a better assimilation of nutrients, it is necessary the use of biostimulants that help to an efficient nutrition, being necessary its application in adequate dose and time and that also promote the development and yield of the crop production, which is obtained a better profitability, achieving this way a greater economic profit.